Pancreatography in chronic pancreatitis: international definitions. Issue 10 (October 1984) - Axon, A T; Classen, M; Cotton, P B; Cremer, M; Freeny, P C; Lees, W R
Abstract : Terminology in classification of pancreatograms was discussed at a recent international workshop on chronic pancreatitis. A new terminology based on morphological radiographic appearances and a new classification to describe the severity and localisation of pancreatogram changes were agreed. Pancreatograms in chronic pancreatitis are graded as normal or equivocal, or as showing mild, moderate, or marked changes, either diffuse or local. It is hoped that these definitions will help communication between centres, serve as a basis for prospective and comparative studies, and facilitate computerisation.